Students' level of boredom, boredom coping strategies, epistemic curiosity, and graded performance. Issue 6 (1st November 2016) - Eren, Altay; Coskun, Hamit
ABSTRACT: The authors examined the relationships among students' levels of boredom, boredom coping strategies, epistemic curiosity, and graded performance regarding mathematics lessons, with the intention to explore the mediating roles of boredom coping strategies and epistemic curiosity in the relationship between the level of boredom and graded performance. A total of 557 students from a small city located in the Western Black Sea region of Turkey voluntarily participated in the study. Of them, 211 enrolled in an Anatolian high school and 346 enrolled in a science high school. Results showed that the level of boredom, boredom coping strategies, epistemic curiosity, and graded performance were significantly related to each other. Results also showed that deprivation-type epistemic curiosity and interest-type epistemic curiosity played significant mediating roles in the relationship between the level of boredom and graded performance. Notably, the mediating roles of interest-type epistemic curiosity and deprivation-type epistemic curiosity differed across gender groups.